A high precision arctangent solution based on CORDIC algorithm - Zhong Yali; Wu Junhui; Liu Xuan; Gao Ping; Duan Xiaohui (Dianzi Jishu Yingyong)
The traditional CORDIC(Coordinate Rotation Computer) algorithm has many iterations, slow convergence speed, and large resource consumption for high-precision arctangent. An improved high-precision CORDIC algorithm is proposed. This method uses the traditional CORDIC algorithm to obtain the sine information after several iterations, and uses the sine value to compensate the error of iteration results，which effectively improves the calculation accuracy. Experimental data shows that the 32 bit improved CORDIC algorithm ensures that the absolute error is less than 5×10-9, the resource consumption of the lookup table is reduced by 64.8%, the resource consumption of the flip-flop is reduced by 35.3%, and the output delay is reduced by 53.3%. In molecular dynamics application scenarios, flip-flop resource consumption can be reduced by 63.2%, and output delay can be reduced by 60%. The improved CORDIC algorithm is superior to the traditional CORDIC algorithm in terms of resource consumption and output delay, and is suitable for high-precision computing applications.